GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey III: South Galactic Pole data release. (6th April 2021) - Franzen, T. M. O.; Hurley-Walker, N.; White, S. V.; Hancock, P. J.; Seymour, N.; Kapińska, A. D.; Staveley-Smith, L.; Wayth, R. B.
Abstract: We present the South Galactic Pole (SGP) data release from the GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey. These data combine both years of GLEAM observations at 72–231 MHz conducted with the Murchison Widefield Array (MWA) and cover an area of 5 113 deg^2 centred on the SGP at 20^h 40^m < RA < 05^h 04^m and -48^° < Dec < -2^° . At 216 MHz, the typical rms noise is ≈5 mJy beam –1 and the angular resolution ≈2 arcmin. The source catalogue contains a total of 108 851 components above 5σ, of which 77% have measured spectral indices between 72 and 231 MHz. Improvements to the data reduction in this release include the use of the GLEAM Extragalactic catalogue as a sky model to calibrate the data, a more efficient and automated algorithm to deconvolve the snapshot images, and a more accurate primary beam model to correct the flux scale. This data release enables more sensitive large-scale studies of extragalactic source populations as well as spectral variability studies on a one-year timescale.